SEMARANG CITY AREA EXPANSION IN 1976: A HISTORICAL STUDY OF HANDLING POPULATION SURGE AND SOCIO-ECONOMIC INEQUALITY-: PERLUASAN WILAYAH KOTA SEMARANG TAHUN 1976: STUDI HISTORIS ATAS PENANGANAN LONJAKAN PENDUDUK DAN KETIMPANGAN SOSIAL-EKONOMI - maurice muafa; Ibnu Sodiq (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This article examines the 1976 Semarang City expansion policy in response to the population surge and socio-economic disparities that emerged in the early New Order era. The study uses a historical-critical approach, drawing on local newspaper archives (Suara Merdeka and Kartika), statistical data from 1973 to 1977, and official regulations (Government Regulation No. 16 of 1976). The research findings reveal that the expansion was initiated locally by Mayor Soepardjo Roestam and later received official approval from the central government. The policy expanded the city's administrative area from approximately 9,742 hectares to 37,366 hectares through the addition of seven new sub-districts. While the expansion succeeded in opening up space for growth and redistributing urban density, it also posed substantial administrative, social, and fiscal challenges. Contemporary media reports highlighted gaps between planning and implementation, including administrative overload at the sub-district level, under-served rural areas, and delayed infrastructure development in newly integrated zones. This article concludes that the expansion of Semarang City in 1976 was a complex spatial planning policy, reflecting the top-down development model of the New Order regime, which prioritized regional expansion as a solution to urban pressures.